A numerical study on the cold sprayability of carbon fibre reinforced composites. Issue 1 (1st February 2023) - Heydari Astaraee, A; Bagherifard, S; Colombo, C
Abstract: One of the open questions in cold spraying on fibre reinforced composites is the optimal thickness of the top layer to provide a suitable base for successful deposition of the metallic particles and at the same time to hinder the probable damage of the fibres. In this study, a detailed finite element model is developed to study the deformation of a single Cu particle deposition on to polyether ether ketone (PEEK) substrate reinforced with carbon fibres. A PEEK layer with 30, 40 or 60 μm thickness was considered on the top surface of the composite. The particle impact velocity was varied in the range of 300-600 m/s to analyse its effects on the induced deformations as well as the structural integrity of the critical carbon fibres. It is believed that the proposed model can provide a helpful tool for predicting the optimal conditions in the metallization of polymers using the cold spray technique.